Implementing Applied Behavior Analysis to Improve Verbal Communication Skills in Children with Speech Delay - Noorhayana, Noorhayana; Suparno, Suparno (Journal of Innovation and Research in Primary Education, 2025)
Verbal communication skills are essential for early childhood development, yet speech delays remain prevalent in early childhood education settings. This classroom action research investigated the effectiveness of Applied Behavior Analysis (ABA) methods in improving verbal communication skills among children with speech delays in mainstream kindergarten settings. Following the Kemmis and McTaggart model, the study was conducted across three cycles at TK Negeri 2 Muara Ancalong with three purposively selected participants aged 5-6 years exhibiting speech delays. Data were collected through direct observations, verbal communication tests, interviews, and documentation, then analyzed using qualitative descriptive methods and quantitative percentage calculations. Results demonstrated substantial improvements, with mean communication scores increasing 96% from baseline (4.33) to Cycle III (8.5). Participants progressed from primarily gestural communication to spontaneous verbal expression and simple sentence construction. The distribution of developmental categories shifted dramatically: Low category decreased from 66.7% (pre-cycle) to 0% (Cycles II-III), while High category increased from 0% to 33.3%. Systematic application of ABA techniques—including positive reinforcement, discrete trial training, and naturalistic teaching—proved effective within regular classroom contexts. The study demonstrates that classroom teachers can successfully implement evidence-based behavioral interventions to address speech delays, extending ABA's applicability beyond specialized therapeutic settings and contributing practical strategies for inclusive early childhood education.